2014
DOI: 10.1142/s0219455414500084
|View full text |Cite
|
Sign up to set email alerts
|

Wind-Induced Response and Universal Equivalent Static Wind Loads of Single Layer Reticular Dome Shells

Abstract: Wind pressure measurements were carried out for dome roofs with di®erent rise-span ratios (f=L ¼ 1=4; 1=6; 1=8) in a boundary wind tunnel. A parametric study was conducted to investigate the in°uences of wind loading and structural parameters on the wind-induced response and the universal equivalent static wind loads (ESWLs) of single-layer reticular dome shells, including the span, rise-span ratio, roof mass and the mean wind velocity. Results show that the rise-span ratio has a signi¯cant in°uence on the win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…However, it may nullify itself if all the POD modes are greatly outnumbered by a wealth of WISRs in the complex linear structures for the greater errors between the accurate { r e } and the approximate WISRs subjected to { P E , f-u } (Sun et al, 2015), that is, the POD reduced-order talent will be even more eclipsed here. Another problem with the method is that only the background ESWLs can be computed in the articles of (Holmes, 1992, 2002, Ginger et al, 2000, Chen et al, 2006, 2012, 2014, Yang et al, 2013, Blaise and Denoel, 2013), and it doesn’t consider structural mechanical behavior and a possible resonant contribution in WISRs (Blaise and Denoel, 2013).…”
Section: The Methods Based On Wisrsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it may nullify itself if all the POD modes are greatly outnumbered by a wealth of WISRs in the complex linear structures for the greater errors between the accurate { r e } and the approximate WISRs subjected to { P E , f-u } (Sun et al, 2015), that is, the POD reduced-order talent will be even more eclipsed here. Another problem with the method is that only the background ESWLs can be computed in the articles of (Holmes, 1992, 2002, Ginger et al, 2000, Chen et al, 2006, 2012, 2014, Yang et al, 2013, Blaise and Denoel, 2013), and it doesn’t consider structural mechanical behavior and a possible resonant contribution in WISRs (Blaise and Denoel, 2013).…”
Section: The Methods Based On Wisrsmentioning
confidence: 99%
“…Therefore, equation (39) is multiplied by an adjustment factor β to express the total UESWLs for all member stress (Chen et al, 2018):In equations (39) and (40), the approximate and simple expressions of { φ k ( x , y )}can be found in Chen et al (2018). C k , f can be obtained like Chen et al (Chen et al 2012, 2014) and Yang et al (2013) in principle. However, to facilitate engineering application, the parametric results of the UESWLs can be simply expressed.…”
Section: The Methods Based On Wisrsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that the type of dome does not significantly affect the deformation of the model. Chen et al (2014) examined the wind induced response and equivalent wind static load on lattice dome structures with different aspect ratio. The results of the study showed that rise-to-span had an important role on the wind pressure distribution of the roof.…”
Section: Introductionmentioning
confidence: 99%
“…Nakayama et al (1998) proposed a method to choose a few vibration modes to calculate the wind-induced responses of domes. Chen et al, (2006Chen et al, ( , 2012Chen et al, ( , 2014 presented the Ritzproper orthogonal decomposition (POD) method to calculate the wind-induced responses of long-span roof structures. In order to cast a more convenient and physically meaningful description, dynamic wind loads are separated into background (quasi-static) and resonant components based on their frequency content (e.g.…”
Section: Introductionmentioning
confidence: 99%